Optimization of abdominal wall reconstruction in patients with complex hernia after oncologic surgery: comparative analysis of surgical techniques and prosthetic materials - a systematic review - Mercado, Zeus Adrian Daniel Alfonso Gonzalez; Zuluaga, Mauricio Zuluaga; Muriel, Santiago Zuluaga; Gómez, María Alejandra Puello; Soto, Simón Ali Ruiz; Aranda, Edison Renato Pereira; Duque, Nicolás Largacha; Arriola, Juan Diego Angulo; Mendoza, Wendy Johana Jacome; Michuy, Melany Nicoll Verdezoto (International Journal of Research in Medical Sciences, 2025)
Abdominal wall reconstruction (AWR) following oncologic resection presents unique surgical challenges, particularly in patients with complex hernias characterized by large defects, contamination, prior mesh infections, or loss of domain. These reconstructions demand techniques that ensure durable structural integrity, minimize recurrence, and accommodate high-risk postoperative environments. A comprehensive literature search was conducted using PRISMA guidelines, including 14 primary studies and 2 systematic reviews published between 2020 and 2025. Studies included adult oncologic patients undergoing AWR with various techniques, prosthetic materials, and perioperative protocols. Risk of bias was assessed using JBI, ROBINS-I, and RoB 2 tools. The reviewed studies demonstrate that the transversus abdominis release (TAR) technique significantly reduces hernia recurrence (2.5% TAR versus 22.5% ACS, p<0.001) and wound complications. Robotic-assisted repairs resulted in reduced pain and hospital stays but incurred longer operative times and higher costs. Biologic meshes were favoured in contaminated fields but showed higher recurrence and cost compared to synthetics. Combined synthetic-biologic approaches in sarcoma patients yielded 0% recurrence with acceptable morbidity. ERAS protocols consistently reduced hospital length of stay and hernia rates (ERAS: 10.1% versus non-ERAS: 28.8%, p=0.008). Sarcopenia and hypoalbuminemia emerged as key predictors of poor surgical outcomes. Optimal AWR in oncologic patients with complex hernias requires individualized strategies that incorporate advanced surgical techniques, judicious mesh selection, and standardized perioperative care. TAR, prophylactic mesh placement, and ERAS protocols show the most promise in improving long-term outcomes. Further randomized trials are warranted to strengthen evidence for best practices.